Serum neurofilament light chain in behavioral variant frontotemporal dementia. (9th October 2018) - Steinacker, Petra; Anderl-Straub, Sarah; Diehl-Schmid, Janine; Semler, Elisa; Uttner, Ingo; von Arnim, Christine A.F.; Barthel, Henryk; Danek, Adrian; Fassbender, Klaus; Fliessbach, Klaus; Foerstl, Hans; Grimmer, Timo; et al.
Abstract : Objective: To determine the association of serum neurofilament light chain (NfL) with functional deterioration and brain atrophy during follow-up of patients with behavioral variant frontotemporal dementia (bvFTD). Methods: Blood NfL levels from 74 patients with bvFTD, 26 with Alzheimer disease (AD), 17 with mild cognitive impairment (MCI), and 15 healthy controls (Con) at baseline and follow-up were determined and analyzed for the diagnostic potential in relation to functional assessment (Clinical Dementia Rating Scale Sum of Boxes [CDR-SOB], frontotemporal lobar degeneration–related CDR-SOB, Mini-Mental State Examination [MMSE]) and brain volumetry. Results: At baseline, serum NfL level correlated with CSF NfL (bvFTD r = 0.706, p < 0.0001; AD/MCI r = 0.666, p = 0.0003). Highest serum levels were observed in bvFTD ( p <0 0.0001 vs Con and MCI, p = 0.0078 vs AD, respectively). Discrimination of bvFTD from Con/MCI/AD was possible with 91%/74%/74% sensitivity and 79%/74%/58% specificity. At follow-up, serum NfL increased in bvFTD and AD ( p = 0.0039 and p = 0.0006, respectively). At baseline and follow-up, NfL correlated with functional scores of patients with bvFTD (e.g., CDR-SOB [baseline] r = 0.4157, p = 0.0006; [follow-up] r = 0.5629, p < 0.0001) and with atrophy in the gray and white matter of many brain regions including frontal and subcortical areas (e.g., frontal lobe: r = −0.5857, p < 0.0001; 95% confidence interval −0.7415 to −0.3701). For patients with AD/MCI, NfL correlated with the functional performance as well (e.g., CDR-SOB [baseline] r = 0.6624, p < 0.0001; [follow-up] r = 0.5659, p = 0.0003) but not with regional brain volumes. Conclusions: As serum NfL correlates with functional impairment and brain atrophy in bvFTD at different disease stages, we propose it as marker of disease severity, paving the way for its future use as outcome measure for clinical trials. Classification of evidence: This study provides Class III evidence that for patients with cognitive problems, serum NfL concentration discriminates bvFTD from other forms of dementia.